Phylogenetic analysis of the neotropical Pseudopolybia de saussure, 1863, with description of the male genitalia of pseudopolybia vespiceps (Hymenoptera: Vespidae, Epiponini) - Andena, Sergio R.; Noll, Fernando B. [UNESP]; Carpenter, James M.; Zucchi, Ronaldo (American Museum of Natural History (BioOne sponsored), 2007)
The male genitalia of Pseudopolybia vespiceps are described and compared to congeners. Characters of the male genitalia are combined with morphological characters of the females and nests and used in a phylogenetic analysis. The single cladogram resulting supports monophyly of the genus Pseudopolybia and interrelationships among the species as: P. langi + (P. difficilis + (P. compressa + P. vespiceps)). A new, illustrated identification key is presented. Copyright © American Museum of Natural History 2007.